Relationship between Moral Intelligence and Wisdom in a Sample of Students in Umm Al-Qura University in light of Some Variables - Alribi, Mohammed Ahmed; Shraideh, Mohammed Khalifa (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the level of moral intelligence and the level of wisdom among a sample of Umm Al-Qura University students, to verify the relationship between moral intelligence and wisdom, and to clarify the differences according to each of the sex variables, specialization (Scientific, literary), academic level (first year, fourth year), and the sample consisted of (277) students of Umm Al-Qura University for the academic year 1436-1437 AH for the bachelor’s stage.. The results showed that the moral intelligence of university students was at an average level, and the wisdom of the sample was at a high level, and there is a positive correlation relationship with statistical significance between the degrees of moral intelligence and wisdom, and wisdom can be predicted through moral intelligence, and there are no statistically significant differences between moral intelligence The wisdom is attributed to the difference in sex, academic specialization and academic level. The study recommends an emphasis on educational institutions to spread moral intelligence, and maintain the level of wisdom among university students, as well integrate their concepts in public and university education curricula.